(untitled) (Journal of Medical & Health Sciences Review, 2025)
Familial hirsutism is a prevalent disorder marked by excessive hair growth in women, often arising from genetic and physiological influences. This research seeks to examine the molecular factors contributing to familial hirsutism in the southern region of Khyber Pakhtunkhwa (KPK), Pakistan. A cross-sectional analysis was conducted involving female participants with a familial history of hirsutism. Biochemical markers such as androgen levels (testosterone, dehydroepiandrosterone sulphate), indicators of insulin resistance, and hormonal profiles were assessed. The results demonstrate increased androgen levels and insulin resistance in the affected individuals relative to the control group. Family pedigree analysis revealed a significant hereditary pattern related to genetic predisposition. The findings indicate that hormonal imbalances and genetic variables are pivotal in the occurrence of familial hirsutism within this community. Comprehending these characteristics might facilitate the formulation of focused treatments and enhance management techniques for impacted persons. Additional investigation is advised to examine the fundamental genetic pathways and possible environmental factors.